Russia’s Policy in the Sphere of External Labor Migration: Management Problems - M. A. Burda (Управление)
The author analyzes the policy of the Russian Federation in the sphere of external labour migration, reveals the peculiarity of formation of the Russian labor market for foreign workforce, focusing on its basic focus on the integration model of the Eurasian economic Union and the Commonwealth of independent States. The article discusses the scheme of formation of migration policy and identifies a number of problematic issues of management of external labour migration, which the author attributed the imperfection of the migration system and peculiarities of political processes in the post-Soviet space. According to the author, this approach is not conducive to quality development of external labour migration, however, is one way of lobbying foreign policy interests in the post-Soviet space. In turn, Central Asian autocrats are interested in the maximum outflow of the economically dissatisfied citizens to prevent anti-state speeches. The quality of the existing risks management of external labor migration indicates the potential of growth of popularity of right-wing political forces and destabilization of the Russian political system. Taking into account the need to balance national security interests and supported by loyal Russian foreign political elites, the author proposes to separate the management of migration on the field of law enforcement and socio-economic part, which requires a political decision of government institutions. Proposed dualism in the author’s opinion, will promote increase of efficiency of counteraction of illegal migration and activation mechanisms, presence on the labour market demand for migrants. As a tool of migration management, the author highlights the Institute of international agreements, the potential of which is currently used does not fully.